Assessing the Existence of Gravity Model for Bangladesh’s Trade: A Panel Data Analysis - Maruf, MD. Kamrul Hasan; Saha, Subrata; Baten, Md. Rakibul Hasan; Akter , Dilruba (South Asian Journal of Social Sciences and Humanities, 2020)
Generally, Gravity model has an important dominance in bilateral trade performance. The foremost intention of this paper is to justify the theory of Gravity model on Bangladesh’s trade activities with its sixty major bilateral trading partner countries including all members of NAFTA and SAARC by applying panel data estimation approach for data 2001 to 2015. This deed estimates the relationship between the total trade (sum of export and import) of Bangladesh with its trade partner and their size of the economies and the transportation cost of trade as proxy of distance between the trading countries. The findings of the study conclude that the shape of the trading countries’ economies has positive significant impact on their bilateral trade and cost of transport is examined a meaningful factor that it has negative impact on Bangladesh’s trade. The study comes across with the visualization that gravity theory has persistency with the trade of Bangladesh. In Bangladesh, the country specific effect indicates it is better for Bangladesh to trade with its neighboring countries rather than trading with less distance countries as the dummy coefficient of SAARC member countries is more positive significant than NAFTA member long distance countries.